Afatinib versus gefitinib or erlotinib in first-line setting for Malaysia patients with EGFR mutant advanced lung adenocarcinoma - Chai, Chee Shee; Liam, Chong Kin; Lin, O. Po; Pang, Yong Kek; Ho, G. F.; Alip, A.; Wong, C. K.; Poh, M. E. (Oxford University Press, 2019)
Abstract Background Afatinib is an irreversible second-generation epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitor (TKI) while gefitinib or erlotinib are reversible first-generation EGFR-TKIs.